Determinan Kepuasan Pasien terhadap Layanan Kesehatan di RSKB Columbia Asia Pulomas Tahun 2024 - Hersyaf, Ryan Aidil (J-Mestahat, 2025)
Background: Hospitals, as public services, can damage their image if the service provided does not meet the public's expectations, as reflected in complaints through the mass media and social networks. One of the improvement efforts is through surveys to measure patient satisfaction. Research Objective: To identify the factors that affect patient satisfaction with healthcare services in the Inpatient Ward at RSKB Columbia Asia Pulomas in 2024. Method: A quantitative study with an analytical observational approach, using purposive sampling techniques and involving 106 respondents. Data was collected through questionnaires and analyzed with univariate, bivariate (chi-square test), and multivariate (multiple linear regression) analyses. Main Results: Based on the analysis of the five service quality dimensions (tangible, empathy, reliability, responsiveness, assurance), the average patient assessment of RSKB Columbia Asia's services was good to very good. The bivariate analysis showed that gender (p-value: 0.293), age (p-value: 0.124), length of stay (p-value: 0.124), and employment (p-value: 0.983) were not related to patient satisfaction. The multivariate analysis indicated that age had the greatest influence on patient satisfaction (beta: 0.295, p-value: 0.002). Main Conclusion: Both male and female patients tended to have similar levels of satisfaction, age differences were not the main factor affecting how patients rated healthcare service quality, length of stay did not directly affect patient satisfaction, and both employed and unemployed patients had relatively the same level of satisfaction. Recommendations: Hospital leadership should emphasize the importance of empathy in every aspect of service and set an example by interacting empathetically with both staff and patients.